Spectacle Lenses With Highly Aspherical Lenslets for Slowing Myopia: A Randomized, Double-Blind, Cross-Over Clinical Trial: Parts of these data were presented as a poster at the Annual Research in Vision and Ophthalmology meeting, 2022 - Sankaridurg, Padmaja; Weng, Rebecca; Tran, Huy; Spiegel, Daniel P; Drobe, Björn; Ha, Thao; Tran, Yen H; Naduvilath, Thomas (American journal of ophthalmology, 2023)
To evaluate myopia progression with highly aspherical lenslet (HAL) spectacles vs conventional single vision (SV) spectacles. Prospective, double-blind, single-center, randomized, cross-over trial. A total of 119 Vietnamese children (7-13 years of age, spherical equivalent refractive error [SE] = -0.75 to -4.75D) were randomized to wear either HAL or SV, and after 6 months (stage 1) crossed over to the other lens for another 6 months (stage 2). At the end of stage 2, both groups wore HAL for a further 6 months. In the order that lenses were worn at each stage, group 1 was designated HSH (HAL-SV-HAL) and group 2 SHH (SV-HAL-HAL). The main outcome measures were a comparison between HAL and SV for change (Δ) in SE and axial length (AL) during each stage; and a comparison of ΔSE/AL with SV between HSH and SHH groups to determine whether myopia rebounded when switched from HAL to SV (HSH group). Myopia progressed more slowly with HAL than with SV during stages 1 and 2 (SEΔ stage 1: -0.21 vs -0.27D, P = .317, stage 2: -0.05 vs -0.32D, P < .001; ALΔ stage 1: 0.07 vs 0.14 mm, P = .004; stage 2: 0.04 vs 0.17 mm, P < .001). ΔSE/AL with SV was not different between the HSH and SHH groups (ΔSE -0.33 ± 0.27D vs -0.27 ± 0.42D, P = .208; ΔAL 0.17 ± 0.13mm vs 0.13 ± 0.15 mm, P = .092). An average of 14 hours per day of lens wear was reported with both lenses. In this cross-over trial, intergroup and intragroup comparisons indicate that HAL slows myopia. Children were compliant with lens wear, and data were not suggestive of rebound when patients were switched from HAL to SV.